Climate-induced variation in a temperature suitability index of chub mackerel in the spawning season and its effect on the abundance - Wang, Liangming; Ma, Shuyang; Liu, Yang; Li, Jianchao; Sun, Dianrong; Tian, Yongjun (Frontiers in Marine Science, 2022)
Chub mackerel (Scomber japonicus) is widely distributed in the northwestern Pacific Ocean and is utilized by China, Korea, and Japan in different seasons and areas. Generally, chub mackerel is divided into Tsushima Warm Current (TWC) and Pacific stocks based on its different distribution, migration, and life-history traits. The two stocks showed obvious interannual to decadal variability in abundance with evident different variation patterns. Chub mackerel has extensive spawning areas in the northwestern Pacific Ocean, with the main spawning period from March to June, and the suitable spawning SST (sea surface temperature) ranging from 15°C to 22°C. To explore the temperature effects on different variations of the two stocks, we estimated the average temperature suitability index (TSI) for chub mackerel in main spawning areas during the spawning period from March to June based on the relationship between the probability of spawning and the specific SST. Results showed that the TSIs in the shelf waters of China seas and the waters of the Tsushima Strait displayed simultaneous abrupt changes in the late 1990s for the TWC stock, whereas the TSI in the Pacific coast of Japan had a regime shift in the late 1970s for the Pacific stock. The spatio-temporal variation in spawning temperature suitability may have had an important impact on the recovery of the Pacific stock after the 2000s. We also found that there is a non-stationary relationship between chub mackerel abundance and TSI, which is driven by climate variabilities such as the Siberian High and the Aleutian Low. Moreover, TWC stock showed non-stationary relationship with TSI, and the threshold years was identified in the 1990s, and the non-stationary relationship between TSI and Pacific stock, with thresholds occurring in the late 1970s. Our research provides a reasonable explanation for the variations in the two stocks and their responses to TSI variability and offers an improved understanding of the climate-induced non-stationary relationships between chub mackerel abundance and physical drivers.